Race, racism and psychology : towards a reflexive history - Richards, Graham (Psychology Press, 2011)
This book offers a comprehensive overview of the ways in which Psychology has engaged with 'race' and racism issues since the late 19th century. It emphasizes the complexities and convolutions of the story and attempts to elucidate the subtleties and occasional paradoxes that have arisen as a result. This new edition updates the research contained in the first edition and includes brand new chapters. These additional chapters draw attention to the importance of the South African Black Consciousness movement and `Post-colonial' Psychology, ã explore recent additional historical research on the fears of `hybridisation', contain new material on French colonial psychiatry, and discuss the awkward status of virtually all the language and terms currently used for discussion of the topic. This important and controversial book has proved to be a vital text, both as a point of departure for more in-depth inquiries, and also as an essential reference tool.The additional up-to-date material included in this new edition makes the book an even more valuable resource to those working in and studying psychology, and also for anyone concerned with the `race' issue either professionally or personally.